Pemlastis epoksi ester minyak sawit sebagai pengganti epoksi minyak kedelai pada kulit imitasi - Utami, Ratri Retno; Satwikanitya, Pani; Saputra, Andri; Syabani, Muh Wahyu; Indahwati, Luthfi Auliya; Ilmannafia, Danuraja (Jurnal Agrotek Ummat, 2024)
A plasticizer is a liquid added to synthetic leather materials to make the product softer, more flexible, and easier to process. The development of sustainable plasticizers in this study was achieved using palm oil as the primary raw material. The study aimed to evaluate the application of epoxidized palm oil esters on imitation leather. The epoxidation process used palm oil esters as the base material, with acetic acid, hydrogen peroxide, and amberlite resin as catalysts. The mixture was heated to a temperature of 60 °C and stirred at a speed of 400 rpm for 4 hours. The resulting epoxy oil was then applied to the top layer of imitation leather, and its mechanical properties were tested. Epoxidized palm oil esters replaced 50% and 100% of epoxidized soybean oil the imitation leather. As a control, plasticizers from commercial epoxidized soybean oil were used. The mechanical test results showed that replacing 100% of the epoxidized soybean oil with palm oil esters in synthetic leather did not result in significant differences in longitudinal tensile strength and transverse elongation compared to the control. However, artificial leather with epoxidized palm oil esters demonstrated better tear resistance than the control. Further studies are required to determine the optimal conditions for the epoxidation reaction, fatty acid composition, and stability of epoxidized palm oil esters.